The hazards of unconfined pyroclastic density currents: a new synthesis and classification according to their deposits, dynamics, and thermal and impact characteristics - Lerner, Geoffrey A. (2022)
Pyroclastic density currents (PDCs) that escape their confining channels are among the most dangerous of volcanic hazards. These unconfined PDCs are capable of inundating inhabited areas that may be unprepared for these hazards, resulting in significant loss of life and damage to infrastructure. Despite their ability to cause serious impacts, unconfined PDCs have previously only been described for a limited number of specific case studies. Here, we carry out a broader comparative study that reviews the different types of unconfined PDCs, their deposits, dynamics and impacts, as well as the relationships between each element. Unconfined PDCs exist within a range of concentration, velocity and temperature: characteristics that are important in determining their impact. We define four end-member unconfined PDCs: 1. fast overspill flows, 2. slow overspill flows, 3. high-energy surges, and 4. low-energy detached surges (LEDS), and review characteristics and incidents of each from historical eruptions. These four end-members were all observed within the 2010 eruptive sequence of Merapi, Indonesia. We use this well-studied eruption as a case study, focusing on the villages of Bakalan (13 km south of the volcano) and Bronggang (14 km south of the volcano), which were impacted by slow overspill flows and LEDS, respectively. These two unconfined PDC types are the least described from previous volcanic eruptions, but during the 2010 Merapi eruption the overspill flows resulted in building destruction and the LEDS in significant loss of life. We discuss the dynamics and deposits of these unconfined PDCs, and the resultant impacts. We then use the lessons learned from the 2010 Merapi eruption to assess some of the impacts associated with the deadly 2018 Fuego, Guatemala eruption. Satellite imagery and media images supplementing fieldwork were used to determine the presence of both overspill flows and LEDS, which resulted in the loss of hundreds of lives and the destruction of hundreds of buildings in inundated areas within 9 km of the summit. By cataloguing unconfined PDC characteristics, dynamics and impacts, we aim to highlight the importance and value of accounting for such phenomena in emergency management and planning at active volcanoes.